2016
DOI: 10.1007/s13770-016-9083-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of poly(L-lactic acid) scaffolds coated with chitosan nanoparticles prepared via ultrasonication and ionic gelation techniques

Abstract: In this study, an attempt was made to develop bi-functional constructs serving both as scaffolds and potential delivery systems for application in neural tissue engineering. The constructs were prepared in two steps. In the first step, the bulks of poly (L-lactic acid) (PLLA) in 1, 4-dioxane/water (87:13) were fabricated using liquid-liquid thermally induced phase separation technique. In the next step, the prepared bulks were coated with chitosan nanoparticles produced by two different techniques of ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The porosity measurement [Figure (C)] by ethanol displacement method revealed that the average results were 93.53 ± 1.27% and 90.00 ± 1.50% for the PLA and PLA/MWCNTs/GNFs conduits respectively. Coating the conduits with chitosan nanoparticles significantly ( p < 0.05) decreased the porosity percentages to 84.57 ± 1.37% and 85.78 ± 0.70% for PLA/MWCNTs/GNFs/CNPs and PLA/MWCNTs/GNFs/rhEpo‐CNPs conduits respectively as a result of the microstructural deformation occurred after soaking the conduits into the nanoparticle‐containing media and the pressure used to entrap the nanoparticles …”
Section: Resultssupporting
confidence: 72%
“…The porosity measurement [Figure (C)] by ethanol displacement method revealed that the average results were 93.53 ± 1.27% and 90.00 ± 1.50% for the PLA and PLA/MWCNTs/GNFs conduits respectively. Coating the conduits with chitosan nanoparticles significantly ( p < 0.05) decreased the porosity percentages to 84.57 ± 1.37% and 85.78 ± 0.70% for PLA/MWCNTs/GNFs/CNPs and PLA/MWCNTs/GNFs/rhEpo‐CNPs conduits respectively as a result of the microstructural deformation occurred after soaking the conduits into the nanoparticle‐containing media and the pressure used to entrap the nanoparticles …”
Section: Resultssupporting
confidence: 72%
“…These properties allow chitosan to bound and retain bioactive molecules on its structure (10,11). Chitosan nanoparticle is produced by exploiting different techniques via ultrasonication or ionic gelation (6,12). Ultrasonication arises from acoustic cavitation phenomenon, which generates strong shear forces through the generation of rapid solvent molecule streaming, which leads to cavitation of bubbles and raises shock waves during bubble collapse (12).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan nanoparticle is produced by exploiting different techniques via ultrasonication or ionic gelation (6,12). Ultrasonication arises from acoustic cavitation phenomenon, which generates strong shear forces through the generation of rapid solvent molecule streaming, which leads to cavitation of bubbles and raises shock waves during bubble collapse (12). The shear forces cut 1, 4-glycosidic bonds of chitosan that is aggregated; consequently, the size of particles is reduced in nano-dimension scale (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations